Rumination Syndrome in Children and Adolescents: A Mini Review - Marc Martinez; Sandeep Rathod; Hunter J. Friesen; John M. Rosen; John M. Rosen; Craig A. Friesen; Craig A. Friesen; Jennifer V. Schurman; Jennifer V. Schurman (Frontiers Media S.A., 2021)
Introduction: Rumination syndrome involves recurrent regurgitation of food and is believed to be underdiagnosed with patients experiencing long delays in diagnosis. It can be associated with significant social consequences, high rates of school absenteeism, and medical complications such as weight loss. The primary aims of the current review are to assess the literature regarding prevalence, pathophysiology, and treatment outcomes with a focus on neurotypical children and adolescents.Results: Population studies in children/adolescents, 5 years of age or older, range from 0 to 5.1%. There are fewer studies in clinical settings, but the prevalence appears to be higher in patients with other gastrointestinal symptoms, particularly chronic vomiting. While physiologic changes that occur during a rumination episode are well-described, the underlying cause is less well-defined. In general, rumination appears to have similarities to other functional gastrointestinal disorders including dysmotility, possibly inflammation, and an interaction with psychologic function. While diaphragmatic breathing is considered the mainstay of treatment, pediatric data demonstrating efficacy is lacking, especially as an isolated treatment.Conclusion: Pediatric rumination syndrome remains greatly understudied, particularly regarding treatment. There is a need to better define prevalence in both the primary care and subspecialty clinical settings, especially in patients presenting with vomiting or apparent gastroesophageal reflux. There is a need to determine whether treatment of co-morbid conditions results in improvement of rumination. Diaphragmatic breathing needs to be studied and compared to other competing responses.